The Emergence And Prevalence Of Employee Management Rhetorics: The Effects Of Long Waves, Labor Unions, And Turnover, 1875 To 1992 - Abrahamson, Eric (Academy of Management Journal, 1997)
Five employee management rhetorics have swept U.S. managerial discourse over the last century: welfare work, scientific management, human relations and personnel management, systems rationalism, and organization culture and quality. I tested two competing theses: the performance-gap thesis, according to which the popularity of rhetorics that promise to narrow organizational performance gaps fluctuates with the magnitude of these gaps across organizations, and the pendulum thesis, according to which the popularity of these rhetorics has been related to upswings and downswings in long waves of macroeconomic activity. I measured rhetorics' popularity between 1875 and 1992 using yearly counts of articles. Results suggest that the two theses are in fad complementary.